A general method for synthesizing enzyme–polymer conjugates in reverse emulsions using Pluronic as a reactive surfactant1. Issue 47 (14th June 2015) - Wu, Xiaoling; Ge, Jun; Zhu, Jingying; Zhang, Yifei; Yong, You; Liu, Zheng
<x xml:space="preserve">Abstract</x> A general method was proposed for synthesizing enzyme–Pluronic nanoconjugates and microgels in reverse emulsions formed by using aldehyde-functionalized Pluronic F-127 as a reactive surfactant.